Development of microclimate in the New Holland T6.165 tractor - Jan Hart; Veronika Hartová (Research in Agricultural Engineering, 2023)
A number of stimuli lead to what is termed "seasonal fatigue", where the only firm interconnection is the fact that this form of fatigue only occurs during a certain period of the season. The interior of the cabin and its effect on the machine operator is notable. The microclimate of the environment in which the operator works has a direct impact on his/her condition and, consequentially, the extent of his/her fatigue. The development of microclimate in a modern agricultural machine must be identified, and based on such findings, recommendation should be given regarding procedures for improving the current situation in agricultural technology. For testing, the New Holland T6.165 tractor was therefore selected. The individual measurements show that a certain drop of oxygen occurs in the cabin during the first half hour of driving. This leads to  an increase in CO2, which is in turn caused by the higher ventilation of the given individuals present in the vehicle. To eliminate said drops in O2, the use of oxygen concentrators may be recommended.